PENGGUNAAN MEDIA KARTU HURUF HIJAIYAH UNTUK MELEJITKAN KECERDASAN SPIRITUAL ANAK USIA DINI PADA RA AS-SALAM 03 DHARMASRAYA - mansyur, Wardani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2020)
Hijaiyah alphabetic card is one of an effective media to increase early childhood student’s intelligence, such as spiritual intelligence. The purpose of this study is to find out the use of media hijaiyah alphabetic card in increasing the children’s spiritual intelligence and the children’s response on spiritual intelligence development in RA As-Salam 03 Dharmasraya. This study was condcuted by using classroom action research which has 2 cycles. There are some steps in each cycle: planning, implementation, observation and reflection stages. The research subject of this study are 10 children of 5-6 years old in group B. The data was collected by observation, documentation and performance task. The result of this study shows that the use of media hijaiyah alphabetic card can increase spiritual intellingence by introducing Asmaul Husna, which is introducing hijaiyah letters from ness value in Asmaul Husna. Cyle I showed that there were 4 children who has better result in development and 4 more children has started to develop. In cyle II the children has a better development which showed that 2 children are getting better, 5 children are develop as expected, and 1 child is in progress to develop. There were 7 children felt happy and 1 child felt unhappy. Meanwhile the cyle II showed that 8 children felt happy. In order to develop the spiritual intelligence accelerately, the educators are expected to use media hijaiyah alphabetic card , because it make children easly acquainted and understand the meaning of words in Asmaul Husna.